Pemodelan Tata Kelola Perusahaan pada Industri Rumah Sakit di Indonesia - Purnomo, Ragil; Praptapa, Agung (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2025)
Abstract Corporate governance in hospital is an aspect that is closely related to ensuring the quality of health services. There are several hospital governance problems, including unclear policies and procedures related to patient safety. Non-compliance with established regulations and safety standards can increase the risk of incidents that harm patients. Ineffective leadership often leads to decisions that are not based on data or patient needs, resulting in suboptimal care. A poor risk management system also allows hospitals to fail to identify and manage risks that could endanger patients. A lack of ongoing training and skill updates for staff can result in staff being less prepared to handle emergency situations or changes in medical practice. Hospitals often do not implement risk mitigation plans in providing services, thereby affecting patient safety. This research was conducted with the aim of knowing corporate governance in the hospital industry in Indonesia. The data used was obtained from several references on the internet media in the form of books, journals, articles, and others. The results of this study indicate that corporate governance in hospitals is an important concept that involves various aspects such as management, finance, and regulatory compliance. In addition, a reliable management information system that supports good corporate governance is essential to improve service quality and operational efficiency of hospitals. Regular risk evaluation and transparency in decision-making and hospital operations are integral parts of the Internal Control System (ICS). The implementation of good corporate governance in hospitals can help create a work environment that is safe, efficient and focused on the needs of patients. Companies with better governance tend to experience lower levels of earnings management, suggesting a negative relationship between governance and earnings management practices. This research is expected to be useful and beneficial for related parties. Companies should consider governance mechanisms related to shareholder and board protection to ensure better operational sustainability.